2022
DOI: 10.1111/1365-2435.14085
|View full text |Cite
|
Sign up to set email alerts
|

Root trait shifts towards an avoidance strategy promote productivity and recovery in C3 and C4 pasture grasses under drought

Abstract: 1. Plant species show a broad spectrum of plasticity in their covarying root traits in response to soil water limitation ranging from no change to shifts towards traits that enhance water and nutrient acquisition. Knowledge of root trait correlations and associated trait plasticity under drought is crucial to sustaining grassland production, including rangelands and pastures, under future, drier climates.2. Here, we investigated below-ground responses to drought in four C 3 and three C 4 grasses and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 158 publications
0
8
1
Order By: Relevance
“…However, the greater drought sensitivity of BNPP relative to ANPP observed in our study supports findings from grassland studies elsewhere ( Frank, 2007 ; Carroll et al , 2021 ), although there have been contrasting responses observed for f BNPP and RMF. This finding is at odds with expectations based on the functional equilibrium theory ( Lambers, 1983 ), whereby plants are expected to increase f BNPP ( Hui and Jackson, 2006 ; Franco et al , 2020 ) and RMF ( Poorter et al , 2012 ; Eziz et al , 2017 ) in response to drought since a greater proportional biomass investment belowground can increase the acquisition of water and other soil resources ( Wilcox et al , 2015 ; Zhang et al , 2017 ; Chandregowda et al , 2022a ). The observed reduction in BNPP and f BNPP in our study might be due to the large drought effect size on aboveground physiology, such as a reduction in leaf water potential and associated impacts on overall plant C assimilation (reported in Jacob et al , 2022 ) and the resulting decrease in the availability of carbohydrates to invest in belowground production.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…However, the greater drought sensitivity of BNPP relative to ANPP observed in our study supports findings from grassland studies elsewhere ( Frank, 2007 ; Carroll et al , 2021 ), although there have been contrasting responses observed for f BNPP and RMF. This finding is at odds with expectations based on the functional equilibrium theory ( Lambers, 1983 ), whereby plants are expected to increase f BNPP ( Hui and Jackson, 2006 ; Franco et al , 2020 ) and RMF ( Poorter et al , 2012 ; Eziz et al , 2017 ) in response to drought since a greater proportional biomass investment belowground can increase the acquisition of water and other soil resources ( Wilcox et al , 2015 ; Zhang et al , 2017 ; Chandregowda et al , 2022a ). The observed reduction in BNPP and f BNPP in our study might be due to the large drought effect size on aboveground physiology, such as a reduction in leaf water potential and associated impacts on overall plant C assimilation (reported in Jacob et al , 2022 ) and the resulting decrease in the availability of carbohydrates to invest in belowground production.…”
Section: Discussionmentioning
confidence: 63%
“…Plant functional traits and their plasticity can illustrate multiple aspects of plant strategies, describe how individual species cope with heterogeneous environments, and provide a means of predicting patterns of plant responses to changes in their environment ( Soudzilovskaia et al , 2013 ; Funk et al , 2017 ). For instance, under conditions such as inadequate nutrient supply and water stress, plants can alter their root traits, by increasing specific root length (SRL; root length per unit root dry mass) or reducing root tissue density (RTD; root mass per unit volume) or mean root diameter, to enhance soil resource uptake and maintain plant growth ( Bruelheide et al , 2018 ; Wieczynski et al , 2019 ; Chandregowda et al , 2022a ). Plants can also alter biomass allocation to facilitate the acquisition of growth-limiting resources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… (1) ( Xu et al., 2009 ); (2) ( Chen et al., 2016 ); (3) ( Delfin et al., 2021 ); (4) ( He et al., 2022 ); (5) ( Schneider et al., 2020 ); (6) ( Liao et al., 2022 ); (7) ( Chandregowda et al., 2022 ); (8) ( Slette et al., 2022 ); (9) ( Jongrungklang et al., 2014 ); (10) ( De Bauw et al., 2019 ); (11) ( de Vries et al., 2019 ); (12) ( Brunn et al., 2022 ); (13) ( Preece and Penuelas, 2016 ); (14) ( de Vries et al., 2020 ); (15) ( Santos-Medellin et al., 2021 ). …”
Section: Implications and Future Perspectivesmentioning
confidence: 99%